Radiotherapy for keratoacanthoma of facial skin: A case report and review of literature - Jia, Xiaojing; Ge, Ying; Wang, Hongyong; Ma, Yan (Frontiers in Oncology, 2023)
Background Keratoacanthoma (KA) is a benign tumor that arises from the infundibulum of hair follicles. However, some researchers believe that KA is a subtype of squamous cell carcinoma (SCC) or a borderline tumor. There are two types of KA: single-type and multiple-type. Surgical resection is the first-line treatment for KA. The treatment options for patients with large lesions who are not surgical candidates are limited. We present a case of single-type KA patients with basic diseases and large lesions that were untreatable surgically, but the lesions essentially disappeared after radiotherapy. No recurrences were discovered during the two-year follow-up. Case Description A 62-year-old male patient was admitted to the dermatology department of our hospital in June 2020 due to the discovery of a red papule on the right face two months prior, with occasional itching, which increased gradually. Pathological examination confirmed the diagnosis of KA. Due to the large lesions and underlying diseases, he was transferred to our radiotherapy department for radiotherapy after consultation. Since the surface of the lesion is uneven and close to the corner of the eye, we adopted intensity modulated radiation therapy (IMRT) at the beginning of radiotherapy. Following the reduction of the lesion, superficial electron beam and added a bolus with thickness of 5mm on the surface of the lesion was continued. The target dose: 42Gy/21 fractions (6MV X-ray, 22Gy; 2Gy/fraction; a total of 11 fractions, 6MeV electron beam, 20Gy; 2Gy/fraction; a total of 10 fractions). By the end of radiotherapy, the patient’s facial tumor was dry and subsided. The facial tumor subsided significantly two years after radiotherapy, and the damaged skin on the face recovered to a flat shape. Conclusions The treatment experience of this case shows that IMRT combined with superficial electron beam radiotherapy may be an effective treatment for single-type KA patients with basic diseases and large lesions that are not suitable for surgery, and it is worth further study.